Anti-cancer activity of asiatic acid against human cholangiocarcinoma cells through inhibition of proliferation and induction of apoptosis - Sakonsinsiri, Chadamas; Kaewlert, Waleeporn; Armartmuntree, Napat; Thanan, Raynoo; Pakdeechote, Poungrat (Cellular and Molecular Biology, 2018)
Plant-derived anti-cancer agents have been of considerable interest due to their promising effectiveness with low side effects. Asiatic acid, the main constituent of the medicinal plant Centella asiatica (L.) Urban, has a wide range of biological properties such as antioxidant, anti-inflammatory and anti-cancer activities. Cholangiocarcinoma (CCA), which is a malignant tumor of bile duct epithelium, is one of the leading cancers in Southeast Asia, notably the northeast of Thailand where the liver fluke, Opisthorchis viverrini predominates. Many in vitro and in vivo studies have provided evidence supporting that oxidative stress induced by chronic inflammation is involved in CCA genesis with aggressive clinical outcomes. This study was performed to evaluate the cytotoxic effects of asiatic acid on two human CCA cell lines (KKU-156 and KKU-213). Cell viability was determined by a sulforhodamine B (SRB) assay. Morphological changes of the cells were observed by microscopy. Cell apoptosis was detected by flow cytometry using annexin V and propidium iodide (PI) staining. Messenger RNA (mRNA) expression levels of BAX, BCL2 and Survivin/BIRC5 were analyzed by real-time polymerase chain reaction (PCR). It was found that asiatic acid efficiently suppressed CCA cellular viability via induction of apoptosis. In addition, the occurrence of asiatic acid-induced apoptosis was confirmed by microscopic observation of apoptotic vesicles, down-regulation of anti-apoptotic genes (BCL2 and Survivin/BIRC5) and increased early and late apoptotic cells. Our results showed the chemotherapeutic activities of asiatic acid, suggesting the anti-cancer properties of this compound should be clinically assessed and its supplementation may lead to an improvement of survival of CCA patients.